Time-dependent reliability of corroded circular steel tube structures: Characterization of statistical models for material properties. (October 2021) - Jiang, Yanju; Song, Biao; Hu, Jiyue; Liang, Hongjun; Rao, Shu
Abstract: The tubular steel structure is one of the most commonly used structural forms exposed in corrosive environments and its structural reliability should be addressed accordingly. However, the materials properties of corroded steel tubes were implicitly represented by those of corroded steel plates in previous studies. Experimental data and reliability analysis regarding the properties of corroded steel tubes (rather than plates) are still inadequate for reliability study. In response to these issues, this study conducted 96 tensile tests with respect to the different degrees of corrosion in circular steel tubes. Results demonstrated that the fracture mode of the corroded steel coupons changed to brittle fracture, and the necking phenomenon in the failure area gradually disappeared. Ultimate strength, yield strength and corresponding strain were remarkably degraded, and the yield plateau shortened and even disappeared as the degree of corrosion increased. Moreover, normal distribution can represent the yield strength of corroded steel tubes, and this distribution was verified by five hypothesis tests in this study. The mean yield strength of corroded steel presented a quadratic declining tendency at increasing corrosion rates. The time-dependent reliability analysis of corroded steel tubes was conducted in two corrosion scenarios (i.e. atmospheric and marine environments) and six levels of applied loadings (reflecting different safety levels). Finally, a set of trial material safety factors for ensuring sufficient safety margin was assessed, which can provide a reference for related specifications of steel tube structures subjected to atmospheric corrosion and/or marine environments.